Parental age effects on neonatal white matter development - Gale-Grant, Oliver; Christiaens, Daan; Cordero-Grande, Lucilio; Chew, Andrew; Falconer, Shona; Makropoulos, Antonios; Harper, Nicholas; Price, Anthony N.; Hutter, Jana; Hughes, Emer; Victor, Suresh; Counsell, Serena J.; et al. (NeuroImage: Clinical, 2020)
Objective: Advanced paternal age is associated with poor offspring developmental outcome. Though an increase in paternal age-related germline mutations may affect offspring white matter development, outcome differences could also be due to psychosocial factors. Here we investigate possible cerebral changes prior to strong environmental influences using brain MRI in a cohort of healthy term-born neonates. Methods: We used structural and diffusion MRI images acquired soon after birth from a cohort (n = 275) of healthy term-born neonates. Images were analysed using a customised tract based spatial statistics (TBSS) processing pipeline. Neurodevelopmental assessment using the Bayley-III scales was offered to all participants at age 18 months. For statistical analysis neonates were compared in two groups, representing the upper quartile (paternal age ≥38 years) and lower three quartiles. The same method was used to assess associations with maternal age. Results: In infants with older fathers (≥38 years), fractional anisotropy, a marker of white matter organisation, was significantly reduced in three early maturing anatomical locations (the corticospinal tract, the corpus callosum, and the optic radiation). Fractional anisotropy in these locations correlated positively with Bayley-III cognitive composite score at 18 months in the advanced paternal age group. A small but significant reduction in total brain volume was also observed in in the infants of older fathers. No significant associations were found between advanced maternal age and neonatal imaging. Conclusions: The epidemiological association between advanced paternal age and offspring outcome is extremely robust. We have for the first time demonstrated a neuroimaging phenotype of advanced paternal age before sustained parental interaction that correlates with later outcome.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Bayley; Brain development; Diffusion MRI; Newborn; Paternal age; White matter